Immunoglobulin G4-Related Disease Responder Index Correlates With the Risk of 1-Year Relapse in Type 1 Autoimmune Pancreatitis. Issue 6 (July 2021) - Rogger, Teresa Marzia; De Marchi, Giulia; Brozzi, Lorenzo; Amodio, Antonio; Orsolini, Giovanni; de Pretis, Nicolò; Conti Bellocchi, Maria Cristina; Crinò, Stefano Francesco; Gabbrielli, Armando; Ciccocioppo, Rachele; Frulloni, Luca
Abstract : Objectives: Type 1 autoimmune pancreatitis (AIP) is a manifestation of immunoglobulin G4–related diseases (IgG4-RD). To evaluate the activity of the disease, the IgG4-RD responder index (RI) has been created. This study evaluated the IgG4-RD RI as prognostic factor of 1-year disease relapse. Methods: Patients diagnosed with type 1 AIP between January 2012 and December 2016, with available magnetic resonance imaging and IgG4 dosage, were enrolled. Immunoglobulin G4-RD RI was calculated at baseline (time 0), and at 3 to 6 and 12 to 18 months after the end of steroid therapy (time 1 and time 2, respectively). Results: Thirty-three patients were included in the study. Immunoglobulin G4-RD RI was 8.9 (standard deviation [SD], 3.8) at time 0, 2.4 (SD, 3.1) at time 1 ( P < 0.0001 vs time 0), and 4.2 (SD, 3.9) at time 2 ( P = 0.02 vs time 1). Fourteen patients who relapsed within 1 year showed a higher mean value of IgG4-RD RI at time 0 (10.9; SD, 4.3) versus 19 who did not (7.4; SD, 2.6; P = 0.012). This difference was observed also at time 2 (6.8 vs 2.1; P = 0.002). Conclusions: Immunoglobulin G4-RD RI correlates with type 1 AIP disease activity, and it predicts disease relapse within 1 year.